Globalization and social and cultural change [Diwaniyah society as a model] (Journal of the College of Basic Education, 2022)
Our Iraqi country has witnessed great changes that led to a social and economic shiftAnd civilization had a profound impact on the social, economic and administrative institutions ofOn the one hand, and on the behavior of the new Iraqi man on the other hand, and in the light of what has befallen the systemThe recent fundamental social, economic and political changes in Iraq in general and in the regionstudy specifically.This research sheds light on aspects of social and cultural change in the regionstudying. As it seems clear now, there are no scientific studies that dealt with the city of DiwaniyahAccording to the rules of modern sociology and anthropology. This study may represent the beginning of studiesComplementary social and on a larger scale in the future